Resistive Switching: Unraveling the Origin and Mechanism of Nanofilament Formation in Polycrystalline SrTiO3 Resistive Switching Memories (Adv. Mater. 28/2019). Issue 28 (10th July 2019) - Kwon, Deok‐Hwang; Lee, Shinbuhm; Kang, Chan Soon; Choi, Yong Seok; Kang, Sung Jin; Cho, Hae Lim; Sohn, Woonbae; Jo, Janghyun; Lee, Seung‐Yong; Oh, Kyu Hwan; Noh, Tae Won; De Souza, Roger A.; et al.
Abstract : Resistive switching in strontium titanate (SrTiO3 ) generally involves the formation of a highly conducting filament upon application of a suitable applied bias. In article number1901322, Manfred Martin, Miyoung Kim, and co‐workers use in situ transmission electron microscopy to identify the conducting filament phase and the accompanying phase. On this basis they establish not only a thermodynamic model that explains why filaments form (with specific compositions) but also a kinetic model to describe why many filaments are nucleated but only one wins the race.